Evaluating Jokowi's Policy on Alcoholic Drink Investment in Indonesia by using sentiment analysis (Journal of Advanced Research in Social Sciences, 2022)
This paper discusses the evaluation of Jokowi's policy regarding alcoholic drink investment in Indonesia by using sentiment analysis. The source of data used as policy feedback in this study is data from the Twitter API. There were 6,963 tweets taken five days before and five days after Jokowi lifted the policy. The data was then manually annotated as many as 963 tweets by sentiment labels. This study uses NLP Techniques to process the data and uses SVM to classify it. Furthermore, using trained data, this paper labels the rest of the tweets into three groups of sentiments, namely positive, negative, and neutral, to see how much public support or rejection of policies on social media. From the analysis, the alcoholic drink investment policy was not successful. The number of negative sentiments from the public shows that this policy is against the people's will. Negative comments dominated during the period of this study, significantly before the President lifted the policy. Nevertheless, Jokowi's decision to revoke the alcohol investment permit is the right step and has succeeded in reducing negative comments and rejections on social media, especially Twitter. This paper also covers words that are interconnected and related in Twitter to give an overview of the tweet's contents. Before the policy was revoked, many tweets contained a rejection of Jokowi's policies, rejection of the Papuan government, and asked the MUI to suggest Jokowi revoke this policy. After the policy was revoked, the comments were more directed at criticism of the President's attitude, which stated that he hated foreign products but allowed investment in alcohol and had made policies that provoked a public controversy.